2018
DOI: 10.18535/jmscr/v6i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Spectrum of Uterine and Cervical Lesions in Hysterectomy Specimens

Abstract: Leiomyoma 33 cases (66%) was the common histopathoogical finding followed by combined leiomyoma and adenomyosis accounting for 7 cases (14%). Non-specific cervicitis 39 cases (78%) was the common histopathological finding in cervical lesion followed by 3 cases (6 %) of dysplasia cervix. Conclusion:The most common benign lesion in uterus was found to be leiomyoma followed by adenomyosis combined with leiomyoma while non-specific cervicitis was found in cervical lesion in hysterectomy specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…This is similar to the study conducted by Ramachandran et al [36] The most common ovarian histopathological finding was simple follicular cyst. This has also been observed in several previous studies [25,33] . In the current study, a histopathological examination revealed no pathological lesions in the fallopian tubes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to the study conducted by Ramachandran et al [36] The most common ovarian histopathological finding was simple follicular cyst. This has also been observed in several previous studies [25,33] . In the current study, a histopathological examination revealed no pathological lesions in the fallopian tubes.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the specimens contained multiple lesions in the uterus, including ten cases of leiomyoma and adenomyosis. Previous studies reported comparable findings [3,11,20,29,31,33] . In 6.9% of cases, dysfunctional uterine bleeding (DUB) was diagnosed before the operation.…”
Section: Discussionsupporting
confidence: 76%
“…The youngest patient who presented with AUB in our study were 26 years old and oldest were 78 years which is almost similar to the study done by Hyanki et al and Doraiswami et al 12,13 Abnormal uterine bleeding predominantly affects women of perimenopausal (41-50 years) age group because of increased incidence of intrauterine lesions. [17][18][19][20] The commonest myometrial lesion observed in present study were leiomyoma and majority of patients were in the range from 41-50 years age group (56.86%) which is in concordance with other studies done by Praseeda et al and Sapna et al where 33.5% and 55.0% respectively. 21,22 There are many minor factors or causes present AUB in the present study also but these are small number.…”
Section: Discussionsupporting
confidence: 90%
“…In the reproductive age of the females, the cervix is subjected to many neoplastic and non-neoplastic situations. These conditions lead to high degree morbidity and mortality and exist across all ages in reproductive life (3) .…”
Section: Introductionmentioning
confidence: 99%